AN EXAMINATION OF THE ORIGIN OF SISAL FARMING IN MAKUENI, KENYA 1965-2018 - Kivuva, Mark; Njoroge, Ruth; Wekesa, Wafula (IJRDO - Journal of Social Science and Humanities Research, 2022)
According to ADRA, the global sisal production declined by 50% in the year 2018, this is the largest decline recorded since the inception of the crop, therefore this justifies the researcher‟s choice of the period between 1965-2018. The purpose of this study was to document the origin, of sisal farming in Makueni, Kenya between 1965 - 2018. The objectives of the study aim at examining the origin of sisal farming in Makueni. The significance of this study is that the study will add knowledge to the sisal farmers which in turn will earn foreign exchange through exportation this research used few theories for instance theory of historical inquiry which gives a detailed explanation on the history of sisal farming in Makueni, Kenya 1965-2018..